Penyuluhan Manajemen Stress Kerja Pada Perawat di RSUD Bangkinang - Dita Puteri, Ade; Yuristin, Devina; Hamidi, M. Nizar Syarif (COVIT (Community Service of Tambusai), 2023)
Stress is one of the impacts of social change and the result of a modernization process which is usually caused by the proliferation of technology, changes in living arrangements and increasingly severe competence between individuals. It is important for nurses to understand the stress response and how individuals attempt to cope with various factors and situations that cause stress (Arita, 2009). About 60% of hospital employees are nurses. Technically the nurse's task takes up more time because they have to monitor the patient's progress intensively within 24 hours. Thus the role of nurses is increasingly involved in the healing process of patients and service satisfaction for their patients. If nurses are unable to handle the demands in the work environment, physical and emotional fatigue will appear which will ultimately lead to burnout in nurses. Community service activities at Bangkinang Regional Hospital entitled "Counseling on Work Stress Management for Nurses" were carried out well in two meetings, namely on June 28-29 2023, which were attended by 68 participants. Participants in this service are all nurses at Bangkinang Hospital. Keywords: extension; nurse; stress management